VD_FINDINFO Ord / 2012 / 12 vom 21. Juni 2012 - VD Tribunal cantonal (2012)
RETRAIT DE L'EFFET SUSPENSIF, RENTE D'INVALIDITÉ, DÉCISION INCIDENTE | 66 LAI, 97 LAVS, 55 al. 1 LPGA, 55 PA, 94 al. 2 LPA-VD